Does Organic Farming Jeopardize Food and Nutrition Security? - Ghislain B. D. Aihounton; Arne Henningsen (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2023)
The prevalence of organic farming and other sustainability standards is increasing around the globe. While effects of organic farming on productivity, income, and poverty alleviation have been analyzed in numerous empirical studies, its effects on food and nutrition security are not yet understood. Using data from smallholder cotton farmers in Benin, we empirically investigate how adopting organic farming affects their food and nutrition security. Our results indicate that adopting organic farming substantially reduces their food security, while it tends to slightly reduce the nutritional quality of their diets. Evaluating pathways, we find that the decreased food and nutrition security is likely caused by lower household income due to lower income from cotton farming given a smaller land area cultivated with cotton, while a larger land area cultivated with food crops cannot fully compensate for the reduced income from cotton farming. This alarming result illustrates the need for evaluating and eventually improving programs for organic farming in developing countries to ensure that good intentions for more sustainable production practices do not jeopardize the livelihoods of vulnerable smallholder farmers.
Keywords: O13; Q12; Q18; 330; organic farming; food security; dietary diversity; farm households; treatment effects